REVEALING TEACHERS’ BELIEFS OF HIGHER ORDER THINKING SKILLS IN TEACHING READING AT JUNIOR HIGH SCHOOL - Ima Kusumastuti; Endang Fauziati; Sri Marmanto (Universitas Muhammadiyah Semarang, 2019)
Belief that the teachers have is a basic concept which will shape their works and all activities they do in the classroom practices. The way they plan the lesson, the decisions that they make, and the teaching method that they apply in the classroom are highly influenced by their beliefs. As Higher Order Thinking Skills (HOTS) and literary skill become important needs for the students to have in the 21st century learning, the teachers must have sufficient knowledge and understanding about it. This case study is aimed in revealing two Junior High School English teachers’ beliefs about Higher Order Thinking Skills (HOTS) mainly in teaching reading. It also reveals how the two teachers apply their beliefs in teaching practices. The findings suggest that teachers’ personal beliefs about HOTS vary from how the implementation of HOTS which should be conducted in the classrooms.